Extraction, Structural Characterisation, and Immunomodulatory Properties of Edible Amanita hemibapha subspecies javanica (Corner and Bas) Mucilage Polysaccharide as a Potential of Functional Food - Utoomporn Surayot; Sutee Wangtueai; SangGuan You; Subramanian Palanisamy; Warawut Krusong; Charles S. Brennan; Francisco J. Barba; Yuthana Phimolsiripol; Phisit Seesuriyachan (My University, 2021)
This research aimed to extract mucilage polysaccharides (MP) from
Keywords: Mucilage; Amanita; Subspecies; Polysaccharides and Plant Cell Walls